Combatting cyanobacteria with hydrogen peroxide: a laboratory study on the consequences for phytoplankton community and diversity - Weenink, Erik F.; Luimstra, Veerle M.; Schuurmans, Jasper M.; Van Herk, Maria J.; Visser, Petra M.; Matthijs, Hans C. (Frontiers in Microbiology, 2015)
Experiments with different phytoplankton densities in lake samples showed that a high biomass increases the rate of HP degradation and decreases the effectiveness of hydrogen peroxide (HP) in the selective suppression of dominant cyanobacteria. Selective application of HP requires usage of low doses only, accordingly this defines the limits for use in lake mitigation. To acquire insight into the impact of HP on other phytoplankton species, we have followed the succession of three phytoplankton groups in lake samples that were treated with different concentrations of HP using a taxa-specific fluorescence emission test. This fast assay reports relatively well on coarse changes in the phytoplankton community, the measured data and the counts from microscopical analysis of the phytoplankton match quite well. The test was used to pursuit HP application in a Planktothrix agardhii-dominated lake sample and displayed a promising shift in the phytoplankton community in only a few weeks. From a low diversity community, a change to a status with a significantly higher diversity and increased abundance of eukaryotic phytoplankton species was established. Re-inoculation experiments of treated samples with original P. agardhii-rich lake water demonstrated prolonged absence of cyanobacteria, and displayed a remarkable stability of the newly developed post-HP treatment state of the phytoplankton community.